Snakes as a new pet - Oberon, Jake. (Neptune City, NJ : T.F.H. Publications, 1990)
Contains a guide for keeping a snake as a pet, and describes snake housing, nutrition, and species.
Includes index.
Adult
Adult
Keywords: Snakes as pets; Snakes as pets